2016
DOI: 10.1177/0960327115607079
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of grape juice on gastric emptying and renal function from cisplatin-induced acute adverse toxicity

Abstract: Grape skin and seeds contain large amounts of phytochemicals such as polyphenols, resveratrol, and proanthocyanidins, which possess antioxidant activities. Cisplatin is widely used in the treatment of cancer. High doses of cisplatin have also been known to produce acute adverse effects. The aim of this study was to investigate the protective effects of antioxidant properties of whole grape juice (with skin and seeds) on cisplatin-induced acute gastrointestinal tract disorders and nephrotoxicity in Wis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The stability tests of RAH in cancer cells revealed that RAH was hydrolyzed into deacetyl-RAH and subsequently decomposed to release RES and aspirin over 24 h of incubation, suggesting that RAH is able to bear the acidic environment in stomach, avoid enzymatic hydrolysis in small intestine, and incorporate into the colon tissue to perform its antitumor activity. Another study initiated by Ko et al (2016) showed that pretreatment wistar rats with whole grape juice that contains large amounts of RES could induce gastric emptying, improve the tubular dilatation and tubular cell vacuolization in renal tubules, thus bringing beneficial effects in preventing cisplatin-induced gastrointestinal tract disorders.…”
Section: Resultsmentioning
confidence: 99%
“…The stability tests of RAH in cancer cells revealed that RAH was hydrolyzed into deacetyl-RAH and subsequently decomposed to release RES and aspirin over 24 h of incubation, suggesting that RAH is able to bear the acidic environment in stomach, avoid enzymatic hydrolysis in small intestine, and incorporate into the colon tissue to perform its antitumor activity. Another study initiated by Ko et al (2016) showed that pretreatment wistar rats with whole grape juice that contains large amounts of RES could induce gastric emptying, improve the tubular dilatation and tubular cell vacuolization in renal tubules, thus bringing beneficial effects in preventing cisplatin-induced gastrointestinal tract disorders.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, Ko et al evaluated the effect of a whole grape juice (with skin and seeds) in rats treated with cisplatin, a chemotherapeutic drug known to provoke acute GI disorders. Cisplatin treatment decreased significantly the rate of gastric emptying compared with the control group, and pretreatment with grape juice (10 ml/kg body weight) prevented this disturbance (68). …”
Section: Pacs In the Stomachmentioning
confidence: 98%
“…Rather, after pre-treatment with whole grape juice tubular cell vacuolization, tubular dilatation and cast formation in kidney tubules were observed to be slightly improved. 37…”
Section: Grapementioning
confidence: 99%